EFFECTIVENESS OF CHILD-FRIENDLY CITY POLICIES IN THE SPECIAL PROTECTION CLUSTER IN MEDAN - Putri Nil Hakim Siregar; Erika Revida; Hairani Siregar (Universitas Negeri Medan, 2026)
The Indonesian government, through the Ministry of Women's Empowerment and Child Protection (KPPPA), developed a Child Friendly City policy to create a safe environment for children to grow and develop, one aspect of which is through protection against acts of violence. The city of Medan is one of the cities that was used as a pilot for the Child Friendly City project through this regulation. The choice of Medan City was based on the fact that Medan City is one of the largest cities in Indonesia with the largest population of children. This research aims to analyse the effectiveness of the Child Friendly City policy as well as analyse and determine the supporting and inhibiting factors in implementing the Child Friendly City policy in Medan City. This research is qualitative research with data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the Child Friendly City policy, which is devoted to special services in the City of Medan based on indicators of right policy, right implementation, right target, right environment and right process, has not been running effectively. The supporting factors for this policy are the regional government's commitment to conducting policy evaluations, stakeholder involvement, and the implementation of Musrenbang as a forum for community participation, while the inhibiting factors are incomplete socialisation, low community awareness, and budget limitations so that the fulfilment of children's rights and the provision of child-friendly facilities are not yet optimal. Keywords: child-friendly city; special protection; policies